A ordem natural do fado: discurso e personagem em fado alexandrino - Panciarelli, Antonio (2006)
This dissertation belongs to area of literature and literary criticism and deals specifically about analysis of Romanesque prose in Fado Alexandrino, by António Lobo Antunes. In this study, we sought to make an immanent analysis of the work, however without disregarding the ideological, political, historical and social aspects that permeate the romance and are of fundamental importance to the understanding of the fable. The analysis presents a theoretical-analytical procedure, in a way that the privileged theoretical aspects were applied, by aiming: to identify in the romance the characteristics that define it as a post-modern literature; to approach the hybridization of genders: prose and poetry, the polyphony of voices, and also the aspects of intertextuality and, of course, the strong political and social contents. The results obtained allow concluding that Fado Alexandrino cannot be characterized only as Romanesque prose nor framed in a predetermined structure. It is a complex construction in which the author uses features of hybridism, heteroglossy and interdiscursivity elements radiographed by Mikhail Bakhtin and by him denominated as prosaic practices that different uses of language make of discourse, offering them as manifestation of plurality. At last, we can affirm that Fado Alexandrino is a work that gives voice to characters that speak, discuss ideas and seek to reposition themselves in a country that attempted a transformation in ten years that has not occurred for five centuries